2007
DOI: 10.1073/pnas.0610059104
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of learning and memory after activation of cerebral Rho GTPases

Abstract: The mechanism whereby the morphology and connectivity of the dendritic tree is regulated depends on an actin dynamics that, in turn, is controlled by Rho GTPases, a family of small GTP-binding proteins encompassing Rho, Rac, and Cdc42 subfamilies. Cytotoxic necrotizing factor 1 (CNF1), a protein toxin from Escherichia coli, constitutively activates Rho GTPases, thus leading to remodeling of the actin cytoskeleton in intact cells. Here, we show that the modulation of cerebral RhoA and Rac1 activity induced by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
115
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 54 publications
(63 reference statements)
15
115
1
Order By: Relevance
“…Rats that were injected in the intra-dorsal hippocampus with the Rac1 inhibitor NSC23766 prior to conditioned pairing exhibited a strong CPA, demonstrating that RhoA, but not Rac1, was required in aversive memory acquisition. This result is in accordance with a previous study showing that genetic disruption or pharmacological inactivation of the RhoA-ROCK signaling pathway in the hippocampus impaired long-term learning and memory in rats [44] .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Rats that were injected in the intra-dorsal hippocampus with the Rac1 inhibitor NSC23766 prior to conditioned pairing exhibited a strong CPA, demonstrating that RhoA, but not Rac1, was required in aversive memory acquisition. This result is in accordance with a previous study showing that genetic disruption or pharmacological inactivation of the RhoA-ROCK signaling pathway in the hippocampus impaired long-term learning and memory in rats [44] .…”
Section: Discussionsupporting
confidence: 83%
“…They oscillate between a GTP-bound active state and a GDP-bound inactive state and act as molecular switches that control the organization and dynamics of the actin cytoskeleton [18] . Much evidence has demonstrated that the Rho GTPases control the assembly and disassembly of the actin cytoskeleton and regulate actin rearrangements at synapses in response to extracellular signals [19,20] . These findings suggest the possibility that the Rho GTPases may be involved in synaptic actin polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Local injection of CNF1 has been shown to increase dendritic spine density in the rat visual cortex [41]. More importantly, these newly formed dendritic spines appear to be functional, as intracerebroventricular (ICV) injection of CNF1 can persistently (up to 90 days post-treatment) increase hippocampal neurotransmission, long-term potentiation (LTP), and memory in wild-type mice [42][43][44]. These benefits may also translate to other neurological disorders.…”
Section: Direct Modulation Of Rho-gtpases For Ad Treatmentmentioning
confidence: 99%
“…Rho GTPases can be blocked in their activated, GTP-bound state by a bacterial protein toxin from Escherichia coli, named cytotoxic necrotizing factor 1 (CNF1). CNF1 catalyzes the deamidation of a single glutamine residue of the Rho molecules, thus impeding GTP hydrolysis and leading to their persistent activation (Flatau et al, 1997;Schmidt et al, 1997;Diana et al, 2007). Here we have exploited this enzymatic activity to examine whether stimulation of structural rearrangements reinstates experience-dependent plasticity in adult age.…”
Section: Introductionmentioning
confidence: 99%